EFEKTIVITAS PENGGUNAAN MEDIA PEMBELAJARAN KARTU DENGAN METODE TALKING STICK PADA MATERI SISTEM RANGKA UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS XI - Novi Artanti, Imanda; Kuswanti, Nur; Khaleyla, Firas (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
More than half of grade XI science students at SMAN 1 Jombang scored below the minimum mastery criterion on the skeletal-system topic, largely because instruction still relied on a single torso model and printed worksheets that did not accommodate students' varied learning styles. This study aims to examine the effectiveness of card-based learning media combined with the talking stick method in improving grade XI students' cognitive learning outcomes (C1-C3) on skeletal-system material. A one-group pretest-posttest design was applied to 35 grade XI science students at SMAN 1 Jombang, who studied the material using the card medium, the talking stick technique, and the school's existing torso model. Learning outcomes were measured with a ten-item multiple-choice test administered before and after the treatment. The pretest and posttest data were tested for normality using Shapiro-Wilk, then examined using a paired-sample t-test and the normalized gain (%N-gain) formula. The results showed that the average score rose from 67.4 in the pretest to 95.7 in the posttest, with a significant difference confirmed by the paired t-test (t = -16.186; df = 34; Sig. 0.000 < 0.05). The %N-gain reached 86.9 percent, which falls into the effective category.